Isoprenaline modified the lipidomic profile and reduced β-oxidation in HL-1 cardiomyocytes: In vitro model of takotsubo syndrome - Fiserova, Ivana; Trinh, Minh Duc; Elkalaf, Moustafa; Vacek, Lukas; Heide, Marek; Martinkova, Stanislava; Bechynska, Kamila; Kosek, Vit; Hajslova, Jana; Fiser, Ondrej; Tousek, Petr; Polak, Jan (Frontiers in Cardiovascular Medicine, 2022)
Recent studies have suggested a pathogenetic link between impaired mitochondria and Takotsubo syndrome (TTS), which is closely connected with catecholamine overstimulation, poor outcomes, and changes in lipid metabolism. We investigated the changes in lipid metabolism at the level of fatty acid β-oxidation and changes in the intracellular lipidomic spectrum. The immortalized cell line of HL-1 cardiomyocytes was used in this study as an established in vitro model of TTS. The cells were exposed to the non-selective β-agonist isoprenaline (ISO) for acute (2 h) and prolonged (24 h) periods. We investigated the impact on mitochondrial adenosine 5’-triphosphate (ATP) production and β-oxidation using real-time cell metabolic analysis, total lipid content, and changes in the lipidomic spectrum using high-performance liquid chromatography (HPLC) and mass spectrometry. Furthermore, modifications of selected lipid transporters were determined using real-time – polymerase chain reaction (RT-PCR) and/or Western blot techniques. By choosing this wide range of targets, we provide a detailed overview of molecular changes in lipid metabolism during catecholamine overstimulation. The present study demonstrates that acute exposure to ISO decreased ATP production by up to 42.2%, and prolonged exposure to ISO decreased β-oxidation by 86.4%. Prolonged exposure to ISO also increased lipid accumulation by 4%. Lipid spectrum analysis of prolonged exposure to ISO showed a reduced concentration of cardioprotective and an increased concentration of lipotoxic lipid molecules during long-term exposure. Decreased lipid utilization can lead to higher intracellular lipid accumulation and the formation of lipotoxic molecules. Changes in the lipid spectrum can induce pathophysiological signaling pathways leading to cardiomyocyte remodeling or apoptosis. Thus, changes in lipid metabolism induced by excessive doses of catecholamines may cause TTS and contribute to a progression of heart failure, which is at increased risk after a TTS episode.